Global responses to terrorism : 9/11, Afghanistan, and beyond - Buckley, Mary (Mary E. A.); Fawn, Rick (Routledge, 2003)
This book examines how the world has reacted to, and been affected by, the terrorist attacks on September 11th, the ensuing war in Afghanistan and President George Bush's declaration of a 'war on terror' as the 'first war of the 21st Century'.